PENGARUH KEBAHAGIAAN DI TEMPAT KERJA TERHADAP KINERJA MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Laily, Nurul; Nurmayanti, Siti (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
This research was conducted to determine factors that can influence performance. This research aims to empirically test happiness at work on performance through job satisfaction. This research uses primary and secondary data obtained through distributing questionnaires to respondents, who are BPS employees of NTB Province. The population in this study were all employees at BPS NTB Province. This research is quantitative research. The number of samples used was 47 employees which was determined based on saturated sampling techniques. The analysis technique used in this research is structural equation modeling partial least squares (SEM-PLS). The research results show that happiness at work has a positive and significant effect on performance, happiness at work has a positive and significant effect on job satisfaction, job satisfaction has a positive and insignificant effect on performance, job satisfaction is able to mediate the effect between happiness at work and performance.